(untitled) (Orinoquia, 2015)
Semen cryopreservation (i.e. sperm banking) is a technique which is used for both humans and animals; it allows the genetic material which will be used in reproduction to be frozen. This research was aimed at evaluating the effect of three cryoprotectants on the mobility and vitality of post-thaw semen from the trans-Andean, omnivorous fish Brycon henni (Pisces: Characidae). Three cryoprotectants (N,N-dimethylformamide (DMF), dimethyl sulphoxide (DMSO) and ethylene glycol (EG)) were used independently for semen cryopreservation (5% concentration); B. henni semen was packed in 0.5 ml plastic mini-straws. Nineteen sexually-mature males and 116 straws were analysed at Animal Biotechnology Laboratory of Politécnico Colombiano Jaime Isaza Cadavid. A computer-assisted sperm class analyser (SCA) system was used for evaluating fresh and post-thaw semen regarding the following parameters: total motility (TM), progressive motility (PM), curvilinear velocity (VCL), straight line velocity (VSL) and average path velocity (VAP). Post-thaw sperm vitality was evaluated by fluorescence microscopy using the SYBR Green I/PI probe assay. Statistical analysis involved fitting generalised linear models (GLM) and Tukey multiple comparison test was used for comparing means. TM percentages were 96.1±3.3% (fresh semen), 52.7±9.2% (DMF), 59.7±9.3% (DMSO) and 62.1±11.2% (EG), whilst PM percentages were 73.3±14.2 (fresh semen), 11.7±6.7% (DMF), 13.8±6.8% (DMSO) and 15.6±7.8% (EG). There were no statistically significant differences between DMSO and EG, but these were greater than those for DMF (p≤0.05) for both variables. Differences for VCL, VSL and VAP were statistically greater for EG (p≤0.05). DMSO had greater sperm vitality values (82.0±1.9%) compared to DMF (73.5±5.9%) and EG (69.2±6.7%) (p≤0.05). it was thus concluded that DMSO and EG had greater TM and PM percentages than DMF, whilst DMSO produced better results regarding vitality when evaluating post-thaw semen from the trans-Andean, omnivorous fish Brycon henni. Key words: Cryoprotectant; fish; viability; vitality.